From sample to mixed reality: a translational 3D MALDI imaging platform for advanced 3D spatial omics analysis of 3D cell culture disease models - Iakab, Stefania Alexandra; Cordes, Jonas; Enzlein, Thomas; Keller, Florian; Kastner, Kevin; Mulholland, Theresa; Fröhlich, Björn Christian; Gruber, Lars; Cairns, James L.; Schmidt, Stefan; Hafner, Mathias; Schneider, Richard; et al. (Advanced science, 2026)
Human 3D cell cultures, including spheroids and organoids, are essential biological models for translational pharmaceutical and biomedical research. However, their 3D analysis using 2D- matrix-assisted laser desorption/ionization (MALDI) imaging-based spatial metabolomics remains challenging, since end-to-end solutions for 3D-enabling sample preparation, 3D-data processing, 3D-rendering, and 3D-user interaction are lacking. Here, a 3D-MALDI imaging platform and resource that advances each of three pillars is presented: i) the sample preparation introduces custom-designed molds for precise and reproducible embedding and cryosectioning of multiple spheroids and organoids, a substantial improvement over ad hoc or single-sample sectioning workflows; ii) the integrated computational framework that facilitates the generation of high-fidelity volumetric datasets that enable voxel-based analysis for feature discovery, surpassing traditional slice-based 2D analysis; iii) the mixed reality tool enables immersive spatial exploration of molecular distributions in 3D, extending user engagement beyond static 3D renderings. The versatility of the platform is illustrated by its translation to a clinical framework for the molecular profiling of patient-derived colon cancer organoids. Collectively, this integrated approach enables spatial metabolomic analysis in 3D, offers increased throughput, and paves the way for next-generation molecular diagnostics and personalized medicine applications.